ETHICS IN OBSTETRIC PRACTICE - F. A. Chervenak; L. B. McCullough (IRBIS LLC, 2016)
Ethics is an essential dimension of obstetric practice. There is defined medical ethics and the fundamental ethical principles of beneficence and respect for autonomy. We then show how these two principles should interact in obstetric judgment and practice with emphasis on the core concept of the foetus as a patient. We then describe the professional responsibility of obstetric ethics. Obstetricians have beneficence based and autonomy-based obligations to the pregnant patient and beneficence-based obligations to the foetal patient.The result is evidence- based clinical judgement about diagnostic and therapeutic measures that are reliably expected to result in a greater balance of clinical goods over clinical harms. The pregnant woman's autonomy is empowered by offering or recommending medically reasonable alternatives. The informed consent process should be used as a preventive ethics tool.